The role of Rhipicephalus sanguineus sensu lato saliva in the dissemination of Rickettsia conorii in C3H/HeJ mice. - Milhano, Natacha (2016)
Animal models have been developed for the study of rickettsial pathogenesis. However, to understand what occurs during the natural route of rickettsial transmission via the tick bite, the role of tick saliva should be considered in these models. To address this, we analysed the role of tick saliva in the transmission of Rickettsia conorii (Rickettsiales: Rickettsiaceae) in a murine host by intradermally (i.d.) inoculating two groups of susceptible C3H/HeJ mice with this Rickettsia, and infesting one group with nymphal Rhipicephalus sanguineus sensu lato (Ixodida: Ixodidae) ticks. Quantification of bacterial loads and mRNA levels of interleukin-1β (IL-1β), IL-10 and NF-κB was performed in C3H/HeJ lung samples by real-time quantitative polymerase chain reaction (PCR) and real-time reverse transcriptase PCR, respectively. Lung histology was examined to evaluate the pathological manifestations of infection. No statistically significant difference in bacterial load in the lungs of mice was observed between these two groups; however, a statistically significant difference was observed in levels of IL-1β and NF-κB, both of which were higher in the group inoculated with rickettsiae but not infected with ticks. Lung histology in both groups of animals revealed infiltration of inflammatory cells. Overall, this study showed that i.d. inoculation of R. conorii caused infection in the lungs of C3H/HeJ mice and tick saliva inhibited proinflammatory effects.